Enhanced patis production - Asiao, Rino N.; Llanes, Francis DC; Montesa, Christine Marie C.; Pangan, Percival S. (College of Engineering, 1996)
Product: Patis -- Plant location: Rosario, Cavite -- Annual volume of production: 1,540,158 liters -- Annual gross sales: Php 66,785,675 -- Annual income: Php 2,722,522 -- Total capital investment: Php 52,202,796 -- Product unit cost: Php 31.17/750 ml -- Product selling price: Php 32.16 -- Breakeven volume: 2,380,678 bottles -- Breakeven price: Php 32.65